Perjumpaan Penginjil CGK Belanda Dengan Orang Toraja Mamasa: Praktik Metode Penginjilan Arie Bikker Dan Martin Geleijnse serta Relevansinya Bagi Metode Pekabaran Injil Gereja Toraja Mamasa Masa Kini - abialtar (KAMASEAN: Jurnal Teologi Kristen, 2020)
Preaching the gospel by Western mission organizations has given rise to a unique encounter between missionaries and indigenous peoples where they preach the gospel. The problem that arises then is the lack of research into what this encounter is and what it means for church life today. The author examines the encounter of evangelists from de Christelijke Gereformeerde Kerken (CGK) in the Netherlands with the Toraja Mamasa community, especially the To Salu tribe with qualitative research methods by relying on library research and mission history archives in Mamasa. Also conducted interviews with traditional and church leaders in Mamasa. The author found that the encounter between the two evangelists with the To Salu tribe had resulted in a missionary attitude and insight and certain theological characteristics which were then inherent in the history of the Toraja Mamasa Church (GTM) which was the fruit of the CGK evangelism. The author's thesis statement: "The attitude and insight and style of the theology of Bikker and Gelijnse, namely the pattern of Dutch Calvinist theology, then colored the theological features of the Mamasa Toraja Church in the course of its ministry in the context of Toraja Mamasa to the present.”Pemberitaan Injil oleh organisasi misi Barat telah melahirkan pertemuan unik antara misionaris dan masyarakat adat di mana mereka memberitakan Injil. Masalah yang muncul kemudian adalah kurangnya penelitian pada apa yang ditimbulkan oleh perjumpaan tersebut dan maknanya bagi kehidupan gereja saat ini. Penulis meneliti pertemuan penginjil dari de Christelijke Gereformeerde Kerken (CGK) di Belanda dengan komunitas Toraja Mamasa, terutama suku To Salu dengan metode penelitian kualitatif dengan mengandalkan penelitian pustaka dan arsip sejarah misi di Mamasa. Juga melakukan wawancara terhadapa tokoh-tokoh adat dan gereja di Mamasa. Penulis menemukan bahwa pertemuan antara dua penginjil dengan suku To Salu telah menghasilkan sikap misi dan wawasan serta ciri-ciri teologis tertentu yang kemudian melekat dalam sejarah Gereja Toraja Mamasa (GTM) yang merupakan buah penginjilan CGK. Pernyataan akhir penulis: "Sikap dan wawasan serta gaya teologi Bikker dan Gelijnse, yaitu pola teologi Calvinis Belanda, kemudian mewarnai ciri-ciri teologis Gereja Mamasa Toraja dalam perjalanan pelayanannya dalam konteks masyarakat Toraja Mamasa."